Stereoselective Reactions in Preparation of Chiral α-Heteraspiro[m.n]alkanes - Undheim, Kjell (Synthesis, 2015)
The biological importance and wide occurrence of spirane systems in nature have stimulated studies in spirane chemistry. The fundamental spirane framework consists of two monocyclic rings linked in an orthogonal relationship by a common ring carbon. This review covers families of annular α-monoheteraspiranes starting with α-heteraspiro[2.4]heptanes and terminating with α-hetera[5.6]dodecanes; the annular heteroatoms are N, O, or S. The spirane systems are arranged according to the relative size of the two monocyclic rings with highest priority for the smaller ring, Often optically active spiranes are prepared for biological reasons by chemical modifications of natural products related to the spirane to be prepared. Chiral auxiliaries are useful in the introduction and control of stereochemistry in the construction of spiranes as intermediates in the preparation of novel amino acids and nucleosides. Another aspect of chiral spirane chemistry concerns modifications and conformational restrictions introduced in natural carbohydrates, nucleosides, and amino acids.1 Introduction2 Heteraspira[2.m]alkanes3 Heteraspira[3.m]alkanes4 Heteraspira[4.m]alkanes5 Heteraspira[5.m]alkanes
Keywords: α-heteraspiranes; chirons; stereoselective syntheses; spiroannulations; spirocyclic amino acids; spirocyclic nucleosides